Corrosion Resistance Synergistic Appraisal of Titanium-Impregnated Bisphenol A-Type Epoxy Duplex Coating System in Stimulated and Natural Marine Environments of Southeastern Coastal Area of China–Pakistan Economic Corridor - Ishrat Jamil; Humaira Bano; Vinod C. Malshe; Azhar Mahmood; Kamran Khan; Nasir M. Ahmad (Advances in Polymer Technology)
This research endeavor is aimed at developing a protective coating for marine service conditions of the southeastern coastal area of the China–Pakistan Economic Corridor. Bisphenol A-type epoxy-based protective coatings were prepared by impregnating exotic titanium metal microparticles into two different proportions, i.e., 5% and 10% (w/w). Film hardness measurement by pencil test, adhesion measurement by the crosshatch-tape test, chemical and heat resistance test, gloss measurement, natural exposure, and salt spray testing have demonstrated that Ti-enriched coatings have performed better than the virgin epoxy coating. Moreover, scanning electron microscopy has depicted more surface degradation. Fourier transform infrared spectroscopy has indicated higher mass loss and chain scission in the virgin epoxy coating than the Ti-enriched coatings. In addition, these Ti microparticles have filled up the cavities/imperfections, reduced cracking, promoted crosslinking during the curing, and cordoned-off passage of corrodents and moisture, thus improving epoxy resin coating features. These results have widened the scope of Ti-embedded epoxy coatings against atmospheric corrosion for highly corrosive marine sites.